Effects of Dietary Lysine Level on Growth Performance and Protein Metabolism in Juvenile Leopard Coral Grouper (Plectropomus leopardus) - Xiaomei Dou; Yu Liu; Yixiong Cao; Yumeng Zhang; Xinlangji Fu; Junming Deng; Beiping Tan (Aquaculture Nutrition)
An 8-week feeding trial was conducted to evaluate the effects of dietary lysine level on growth performance and protein metabolism of juvenile leopard coral grouper (Plectropomus leopardus) and thereby obtained the optimal dietary lysine requirement of P. leopardus. Six isoproteic and isolipidic experimental diets were formulated to contain 1.10%, 1.69%, 2.30%, 3.08%, 3.56%, and 4.36% lysine of diets, respectively. Each diet was assigned at random to triplicate groups of 25 juveniles (initial mean weight is 10.57 g) per tank in a flow-through mariculture system maintained at 27–30°C. Dietary inclusion of 2.30–3.08% lysine improved the weight gain rate (WGR) and specific growth rate and decreased the feed conversion ratio (FCR) of juveniles (P<0.05). The intestinal digestive enzyme (trypsin, amylase, and lipase) activities were overall enhanced by dietary inclusion of 3.08–3.56% lysine (P<0.05). The mammalian target of rapamycin (mTOR) signaling pathway was activated in fish fed diets with 1.69–2.30% lysine by upregulating the relative expression levels of hepatic TOR and S6K1 (p70 ribosomal protein S6 kinase 1) but downregulating the relative expression level of hepatic 4E-BP2 (eIF4E-binding protein 2). Conversely, the amino acid response signaling pathway was inhibited in fish fed diet with 2.30% lysine by downregulating the relative expression levels of hepatic GCN2 (general control nondepressible 2), ATF3 (activating transcription factor 3), ATF4a (activating transcription factor 4a), and ATF4b (activating transcription factor 4b). Additionally, dietary 1.69–3.08% lysine enhanced the plasma total protein level and hepatic lysine α-ketoglutarate reductase activity but depressed the blood urea nitrogen level and hepatic adenosine monophosphate deaminase activity (P<0.05). Moreover, dietary 3.08% lysine increased the contents of whole-body crude protein and total amino acids, while 1.69%–4.36% lysine depressed the whole-body lipid content (P<0.05). These results indicated that optimal dietary lysine increased the digestive enzyme activities, promoted protein synthesis but depressed protein degradation, and thereby improved the growth performance of P. leopardus. Based on the second-order polynomial model, the optimal lysine requirement of juvenile P. leopardus for WGR, FCR, and lysine deposition was 2.60%–2.97% of diets (4.91%–5.60% of dietary protein).